The Relevance of Paulo Freire’s Liberation Education to the Implementation of the Independent Curriculum in Indonesia - Juppenny, Ryan; Cahyono, Hadi; Hudijono, Singkir; Mahardhani, Ardhana Januar (Jurnal Sustainable, 2025)
Education in Paulo Freire's view has a great urgency as a means of liberation from social, political and economic injustice. This article examines the concept of Paulo Freire education which is oriented to humanization and critical awareness (conscienient) to fight dehumanization. Freire rejected the education model "bank style," which only positioned students as passive objects, and offers a dialogical approach as a solution to create interactive, critical, and relevant learning spaces to social contexts. The method used in this article is the study of literature, by examining various books, journals, and articles related to Freire thought. This study found that liberating education involved dialogue as the core of learning, where the teacher and students both acted as subjects. This process builds critical awareness that allows individuals to understand and change the structure of oppression in society. Education must be relevant to the life experience of students, allowing them to develop critical thinking to understand the root of the problem and take solutive. The results of the discussion show the relevance of the concept of Freire to the free curriculum of learning in Indonesia, which emphasizes the freedom and autonomy of students in exploring the potential of themselves. This article recommends the application of dialogue and reflection -based education as an approach to overcoming the challenges of globalization and improving the quality of education. Thus, education is not only a means of transferring knowledge, but also a tool to empower individuals as agents of social change.